Effect of dust on the solar spectrum and electricity generation of a photovoltaic module. Issue 14 (6th October 2020) - Konyu, Maruphong; Ketjoy, Nipon; Sirisamphanwong, Chatchai
Abstract : The accumulation of dust on any given photovoltaic (PV) module surface depends on the type of dust, environment, surroundings, weather, module properties, and its installation design. In this research, equations were developed for the preliminary evaluation and comparison of the reduction in power from PV modules because of dust soiling. Use of these equations shows that dust accumulation decreases solar irradiance and thus the power output of modules, and that there is a linear relationship between the power output degradation and density or amount of accumulated dust. The equations can be used to conduct analysis of average photon energy and the PV module power output reduction from accumulated dust. The study also showed that type of PV module can also affect the degree of power output reduction. The amorphous silicon PV modules are more affected compared to poly crystalline silicon PV modules as the latter has a spectrum response which still has the range that can produce full energy and therefore, dust soiling has lesser impact on them. PV power plants should regularly clean the modules, if not, production of electricity decreases, and so too the revenue from selling electricity, making the payback of the power plant longer.